Dual-frequency countercurrent ultrasonic-assisted extraction of the cold brew coffee and in situ real-time monitoring of extraction process - Huimin Liu; Dandan Liu; Wuli Wang; Xinyan Zhang; Jamila Tuly; Hanhan Li; Haile Ma (Ultrasonics Sonochemistry)
This research aimed to examine the effect of countercurrent ultrasound on extraction efficiency of cold brew coffee (CBC). The quality and flavor of CBC obtained by ultrasonic-assisted extraction (UE) were evaluated and compared with traditional extraction (TE). Meanwhile, the UE process was monitored in situ real-time using a near-infrared (NIR) spectrometer. The optimal UE parameters obtained by experiments were dual-frequency of 20/28 kHz, countercurrent ultrasonic treatment time of 50 min, ultrasonic power density of 320 W/L, and material-liquid ratio of 1:15. Under the optimal parameters, the total dissolved solids content (TDS) and extraction yield (EY) were 1.63 % and 20.52 %, respectively. This resulted in an 83.33 % improvement in efficiency matching the TDS and EY of a 5-h TE CBC. In comparison with the control, the contents of total polyphenols, total sugars, and total lipids after ultrasonic treatment increased by 13.79 %, 28.49 %, and 333.33 %, respectively, while the total acids content decreased by 27.81 %. HPLC and HS-SPME-GC/MS analysis showed similar non-volatile and volatile flavor components between UE and TE CBC. A quantitative partial least squares (PLS) prediction model was developed to monitor TDS and CGA levels during the UE CBC. This model demonstrated excellent calibration and prediction performance. (TDS: Rc = 0.9281; RMSECV = 0.0694; Rp = 0.9514; RMSEP = 0.0631. CGA: Rc = 0.9086; RMSECV = 0.0316; Rp = 0.9467; RMSEP = 0.0212). This study explored an efficient approach for the industrialization of CBC production and provided theoretical support for developing an intelligent control system for its process.